2022
DOI: 10.1021/acscatal.1c05520
|View full text |Cite
|
Sign up to set email alerts
|

Using pH Dependence to Understand Mechanisms in Electrochemical CO Reduction

Abstract: Electrochemical conversion of CO(2) into hydrocarbons and oxygenates is envisioned as a promising path toward closing the carbon cycle in modern technology. To date, however, the reaction mechanisms toward the plethora of products are disputed, complicating the search for alternative catalyst materials. To conclusively identify the rate-limiting steps in CO reduction on Cu, we analyzed the mechanisms on the basis of constant-potential density functional theory (DFT) kinetics and experiments at a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
112
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 87 publications
10
112
0
Order By: Relevance
“…We derive and validate this mechanism using density functional theory (DFT) calculations. In our derivation, we assume the same rate determining step (RDS) for all C 2 products based on previous experimental and theoretical studies, which has been suggested to either be a CO* dimerization 35–37 or the protonation of the OCCO* intermediate with water as the proton donor. 38 The same RDS is consistent with the range of similar Tafel slopes and the distinguishing lack of an inverse pH-activity relationship shared among the considered C 2 products (ethylene, ethanol, acetate) 11 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We derive and validate this mechanism using density functional theory (DFT) calculations. In our derivation, we assume the same rate determining step (RDS) for all C 2 products based on previous experimental and theoretical studies, which has been suggested to either be a CO* dimerization 35–37 or the protonation of the OCCO* intermediate with water as the proton donor. 38 The same RDS is consistent with the range of similar Tafel slopes and the distinguishing lack of an inverse pH-activity relationship shared among the considered C 2 products (ethylene, ethanol, acetate) 11 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1d , red). Cu(100) surface, known to be active for C–C coupling reactions 46 , was chosen as the model catalyst surface for CH 4 and C 2 H 4 formation paths, as well as Ag(111) surface for CO formation path. At two different potentials of −0.5 V vs. standard hydrogen electrode (SHE) for the potential at point of zero charge ( E PZC ) and −1.0 V SHE for the interface charge of −18 μC cm −2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Monteiro et al showed a lack of CO 2 RR activity to CO without M + , which initiated an intensive discussion about the possibility of CCET 13 . In addition, Chan and coworkers investigated the kinetic importance of proton activity using pH control experiments 12 , 46 . They found that the pH variation significantly changes the CH 4 production rate 46 , while the CO and C 2 H 4 production rates are nearly unchanged on a SHE potential scale 12 , 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical insight uncovered that the deprotonated carboxylate (−COO – ) showed a strong affinity for H 2 O binding, which could activate the H 2 O molecules and promote the protonation of intermediates. The study on the pH dependence of CO elelctroreduction also confirmed that anions with lower p K a ’s than water (like carboxyl) can act as proton donors, which facilitates the protonation of *CO and accelerates the rate-limiting step for methane production. These findings explained the facilitation of methane electroproduction by GSH ligands.…”
mentioning
confidence: 57%